Unhealthy alcohol use and risk of coronary heart disease among young and middle-aged adults - Jamal S. Rana; Felicia W. Chi; Isaac Acquah; Stacy A. Sterling (American Journal of Preventive Cardiology)
Objective: To examine the associations between unhealthy alcohol use and risk of coronary heart disease (CHD) among women and men aged 18–65 years. Methods: An observational study in an integrated healthcare system with systematic alcohol screening. We identified 432,265 primary care patients aged 18–65 years who, in 2014–2015, reported weekly alcohol intake levels. Weekly alcohol intake, categorized into below (≤14/week men; ≤7/week women) and above limits (≥15/week men; ≥ 8/week women) per U.S. guidelines, and heavy episodic drinking (HED, ≥5/≥4 drinks any day in past 3 months for men/women, respectively). Main outcome was CHD during 4-year follow-up, based on inpatient ICD diagnoses of myocardial infarction and CHD. Cox proportional hazards models adjusted for age, sex, race/ethnicity, body mass index, physical activity, smoking, hypertension, diabetes, and hyperlipidemia. Results: The cohort comprised 44 % women, mean age (standard deviation) of 43.5 years (±13.1). Weekly alcohol intake above limits was associated with higher prevalence of cardiovascular risk factors, and a 26 %, 19 % and 43 % higher risk on the overall, men- and women-specific risk of CHD after adjusting for these risk factors (hazard ratio [95 % confidence interval] = 1.26[1.13 -1.40], 1.19[1.04–1.35] and 1.43[1.20–1.71], respectively). Conclusions: In a large, real-world, diverse population with a systematic alcohol screening program, having weekly alcohol intake above limits was associated with increased risk of CHD among young and middle-aged men and women. Increased CHD risk due to alcohol intake above limits warrants particular awareness and interventions.